PENINGKATAN COMMUNICATION SKILLS MELALUI MODEL PEMBELAJARAN TEAM GAMES TOURNAMENT (TGT) DI KELAS VI SDN TINGKIR TENGAH 02 SALATIGA - Aqim Muhaimin Zain; Mawardi Mawardi (Bestari: Jurnal Pendidikan dan Kebudayaan, 2023)
Abstract: One of the skills of the 21st century is communication, communication in education plays a very important role. Communication gets more attention from the public because with good communication, the goals of effective and efficient learning activities can be achieved. The problem of low communication skills in elementary schools (SD) can have a long-term impact on student development. This is in accordance with observations made by researchers in class VI of State Elementary School 02 Salatiga which found several problems, namely that students did not have the initiative to try to answer questions given by the teacher in between lessons, class VI students who were appointed by the teacher to answer questions spoke aloud. who is slow and shows a tense expression. Students also often enjoy themselves in the learning process and do not pay attention to the opinions of other students when asked by the teacher. The research was carried out in two cycles to improve communication skills, in cycle I the students' communication skills increased to 70.37%, namely 7 students in the very good category and 12 students in the good category. So improvements were made in the second cycle of learning and the results reached 85.18%, namely 9 students in the very good category and 14 students in the good category and the very good category. Observation results also show an increase in communication skills, students are more active in asking and answering questions, dare to express opinions and listen to the opinions of other students, apart from that, students also actively collaborate, support and motivate and recognize the contribution of each group member. This research indicates that the use of the Team Games Tournament learning model is an effective learning approach to train and improve communication skills in class VI of SD Negeri Tingkir Tengah 02 Salatiga.Keywords: communication skills, team games tournament Abstrak: Salah satu keterampilan abad 21 yakni komunikasi, komunikasi dalam pendidikan sangat berperan penting. Komunikasi mendapatkan perhatian lebih dari masyarakat karena dengan komunikasi yang baik, tujuan kegiatan pembelajaran yang efektif dan efisien dapat tercapai. Masalah rendahnya kemampuan berkomunikasi di Sekolah Dasar (SD) dapat memiliki dampak jangka panjang pada perkembangan siswa. Hal ini sesuai dengan observasi yang dilakukan oleh peneliti di kelas VI Sekolah Dasar Negeri 02 Salatiga menemukan beberapa permasalahan yaitu siswa tidak memiliki inisiatif untuk mencoba menjawab pertanyaan yang diberikan oleh guru di sela pembelajaran, siswa kelas VI yang ditunjuk oleh guru untuk menjawab pertanyaan berbicara dengan suara yang pelan dan menunjukan ekspresi yang tegang. Siswa juga sering asik sendiri dalam proses pembelajaran dan dan tidak memperhatikan pendapat siswa lain ketika ditanya guru. Penelitian dilakukan dalam dua siklus untuk meningkatkan communication skills, pada siklus I dan communication skills siswa meningkat menjadi 70,37% yaitu 7 siswa dengan kategori baik sekali dan 12 siswa dengan kategori baik. Sehingga dilakukan perbaikan pada pembelajaran siklus II dan hasil mencapai 85,18%  yaitu 9 siswa dengan kategori baik sekali dan 14 siswa dengan kategori baik dengan kategori sangat baik. Hasil observasi juga menunjukkan adanya peningkatan communication skills, siswa lebih aktif bertanya dan menjawab pertanyaan, berani mengemukakan pendapat dan mendengarkan pendapat siswa lain, selain itu juga siswa aktif berkolaborasi, mendukung dan memotivasi serta mengakui kontribusi setiap anggota kelompok. Penelitian ini mengindikasikan bahwa penggunaan model pembelajaran Team Games Tournament adalah salah satu pendekatan pembelajaran yang efektif untuk melatih dan meningkatkan communication skills pada kelas VI SD Negeri Tingkir Tengah 02 Salatiga.Kata Kunci: communication skills, team games tournament